The Behavioral Finance of MSME in Indonesia: Financial Literacy, Financial Technology (Fintech), and Financial Attitudes - Rahayu, Fadilah Siti; Risman, Asep; Firdaus, Iwan; Haningsih, Luna (International Journal of Digital Entrepreneurship and Business, 2023)
The study investigates the critical factors affecting financial behavior in Micro, Small, and Medium Enterprises (MSMEs). It analyzes the role of financial literacy, attitudes, and financial technology (Fintech) on financial management behavior among 1.1 million DKI Jakarta MSME stakeholders in 2020 through random sampling. The study reveals that heightened financial literacy positively influences financial management behavior. A solid foundation in financial knowledge, encompassing personal and corporate finance, leads to improved financial practices. This validates theories about cognitive biases, heuristics, and practical financial decision-making. Additionally, it emphasizes the pivotal role of positive financial attitudes in shaping financial management behavior. Stakeholders with constructive attitudes, such as financial self-control and proactive financial approaches, make sound financial decisions. This aligns with theories of planned behavior, which underscore attitudes in guiding future financial actions. Conversely, the influence of financial technology (Fintech) on MSME financial behavior is limited, primarily due to a lack of awareness and understanding among small and micro-enterprise operators regarding Fintech products and services. This study underscores the importance of promoting financial literacy, nurturing positive financial attitudes, and enhancing Fintech awareness among MSMEs. It offers actionable insights for policymakers, financial institutions, and business support organizations, enabling them to bolster MSMEs’ financial knowledge and practices, thereby supporting their role as economic powerhouses.